ASSA13-03-32 The Alterations of Heart Function and Cardiac Mitochondria in Selenium Deficiency Rats. (29th April 2013) - Ming, Zhang; Jin, Wei; Rui, Yan; Hu, Shan; Xiaoqing, Pan
Abstract : Objective: To study the dynamic changes of heart function and cardiac mitochondria in selenium deficiency rats. Methods: Forty-eight rats were randomised into normal control group (n = 24) and selenium deficiency model group (n = 24). When rats were fed for 10 weeks, 20 weeks, 30 weeks and 40 weeks respectively, selenium levels in the rat blood were determined using fluorescence method, and heart function was measured by carotid artery intubation. At the corresponding time points, the alterations of cardiac mitochondria were observed under electron microscopy, and the mitochondrial stereological parameters including surface density (Sv), volume density (Vv) and specific surface (Rsv, surface-to-volume ratio) were further studied. The cardiac mitochondria were extracted from the rats at the corresponding time points for assessing the enzyme activities of succinate dehydrogenase (SDH) and cytochrome c oxidase (COX). Results: (1) Compared with the corresponding control group, the blood selenium levels, left ventricular systolic pressure (LVSP) and maximum rate of left ventricular pressure rise (+dp/dtmax) in the model group were all decreased ( P as the time of selenium deficiency prolonged ( P, and remarkable increase in Vv in the selenium deficiency rat hearts compared with the corresponding control group ( P mitochondrial stereological parameters and the enzyme activities in the model group were more notable with the time extension of low selenium ( P Sv, Rsv, SDH and COX, and negative correlation with Vv ( P < 0.01). Conclusions: Selenium deficiency leads to the damage of mitochondrial structure and function in rats, resulting in heart failure.